PEMANFAATAN MEDIA SOSIAL TWITTER @METROTVTODAY DALAM MEMBANGUN ENGAGEMENT DENGAN PEMIRSA PROGRAM “PRIME TALK” DI METRO TV - Visca Nurullita; Happy Prasetyawati (Inter Community: Journal of Communication Empowerment, 2019)
This research examines The Utilization of Social Media Twitter in Building Engagement with the audience of "Prime Talk" program on Metro TV. Program talk show which airs at prime time 19:05 – 20:00 WIB, started to utilize social media in the era of media convergence to publish the contents of the program in a way of live tweet. To analyze the results of the research, this research uses the framework of utilizing social media (content, monitoring, amplify, lead) which was stated by McKinsey and engagement structure (consumption, curation, creation, collaboration) stated by Evan & Mckee. The Researcher uses a post-positivistic paradigm with a qualitative approach and descriptive research. The data collection techniques used is observation and interviews. The results conducted indicate that the use of social media twitter has not been done properly so the “Prime Talk” program has not been able to produce the highest level of engagement with it’s viewers on social media.